CXCL9 Predicts Severity at the Onset of Chronic Graft-versus-host Disease. Issue 11 (November 2020) - Giesen, Nicola; Schwarzbich, Mark-Alexander; Dischinger, Katharina; Becker, Natalia; Hummel, Manuela; Benner, Axel; Radujkovic, Aleksandar; Müller-Tidow, Carsten; Dreger, Peter; Luft, Thomas
Abstract : Background: Chronic graft-versus-host disease (cGVHD) represents a double-edged sword. In its nonsevere form, cGVHD associates with better control of the malignant disease, thus highlighting graft-versus-leukemia effects. However, severe cGVHD leads to debilitating morbidity and increased nonrelapse mortality. The prediction of severe cGVHD, in particular at disease onset, is therefore of high importance for ensuing clinical decisions and overall success of allogeneic stem cell transplantations. CXC-chemokine ligand 9 (CXCL9) is an interferon-inducible chemokine of the CXC family and is increased in cGVHD. Endothelial activation and stress index (EASIX) was shown to predict death after acute graft-versus-host disease. We explored CXCL9 and EASIX as predictors of severe cGVHD. Methods: Sera and clinical data of 480 patients were available who survived at least 6 months following allogeneic stem cell transplantation without steroid-refractory acute graft-versus-host disease and without early relapse. CXCL9 and EASIX were measured on day +100 and onset of cGVHD. Results: Development of nonsevere cGVHD was significantly associated with improved overall survival (hazard ratio 0.53, P < 0.001). CXCL9 serum levels at the onset of cGVHD predicted the development of severe cGVHD later on (hazard ratio 1.33, P = 0.02). In contrast, EASIX at the onset of cGVHD was not associated with cGVHD severity but was a significant independent risk factor for overall mortality and nonrelapse mortality. Conclusions: CXCL9 levels at the onset of cGVHD can help to predict severe courses of the disease and have potential for optimizing tailored administration of immunosuppressive therapy. Abstract : Supplemental Digital Content is available in the text.